Hurricane Florence (2018): Long duration single‐ and dual‐Doppler observations and wind retrievals during landfall. (16th November 2021) - Biggerstaff, Michael I.; Alford, A. Addison; Carrie, Gordon D.; Stevenson, Jeffrey A.
Abstract: A ground‐based C‐band Shared Mobile Atmospheric Research and Teaching (SMART) polarimetric radar and the National Weather Service WSR‐88D radar near Wilmington, North Carolina simultaneously observed Hurricane Florence (2018) as it made landfall as a category 1 hurricane. The slow translation of Florence allowed for more than 30 hr of data collection before, during and after the tropical cyclone came ashore. Nearly 26 hr of three‐dimensional wind retrievals every 6–10 min were constructed from the radar observations, providing an unprecedented view of the evolution of rainbands, the inner core and the eyewall of Hurricane Florence. This article describes the radar data, the procedures used for automated quality control, data processing and the wind retrievals that have been constructed. The location of the data and wind retrieval archive is given. These data can be used to study the dynamics and rainfall of Hurricane Florence, to quantify the impact of winds on the natural and built environment, to validate numerical simulations of the tropical cyclone, and as an educational resource for courses in radar and tropical meteorology. Abstract : A SMART radar and a WSR‐88D radar observed Hurricane Florence (2018) for more than 30 hr as it made landfall near Wilmington, North Carolina. Nearly 26 hr of three‐dimensional wind retrievals were constructed every 6–10 min, yielding an unprecedented view of the evolution of rainbands, the inner core and the eyewall of Hurricane Florence. This article describes the radar data, the procedures used for automated quality control, data processing and the wind retrievals that have been constructed.